Pola Komunikasi Antara Orang Tua dan Anak dalam Pembelajaran Daring di Masa Pandemi Covid-19 - Sazili Sazili; Nesthy Kheren Nadia (Departement of Mathematics Education, 2023)
Coronavirus Diseases 2019 (Covid-19) has brought changes in various fields, including education and communication. The teaching and learning process is carried out remotely or online using virtual applications such as Zoom, Google Meet, Google class room and so on. Using media for learning is an effort to increase the efficiency and quality of student learning processes online. Online learning aims to provide quality learning services in a massive and open network to reach more and wider audiences. With online learning for students in their respective homes, of course, there is a role for parents to supervise and guide their children in online learning because online learning is directly connected to the internet. The research method used in this study is a qualitative method that produces descriptive and written data with information from people who produce hypotheses and field research. Informants in the study consisted of 2 women and 1 man. The results obtained in this study are. Children can freely express any complaints they experience to their parents without feeling afraid. Parents must be prepared to become a substitute teacher for the children at home. Parents are demanded to learn more to know and understand online learning carried out by their children. The main media used in online learning is cellphones. while internet connection is one of the main problems that becomes an obstacle in learning through the online system. The barrier to communication is the lack of time and this is caused, because with busy working parents they cannot fully control what their children do with their gadgets. Meanwhile, the way to overcome communication barriers in the family to their children is by starting a conversation with the child, spending a lot of time together so that parents can find solutions to the problems being faced by children in online learning.